The Tendai Debates of 1131 at Hosshōji - Minowa, Kenryō (Japanese journal of religious studies, 2014)
Debate was a key part of many monks' training. It also played a vital role in the competition between Buddhist schools. A good sense of how monks interacted can be gained by looking at one year, 1131, at the debates at Hosshōji. Tendai monks were paired with Nara monks, usually from the Hossō School, to consider various doctrinal issues. In some cases, the root text being discussed can be determined, but often the topic of debate remains obscure because of the terseness of the passage. Sometimes the winner of the debate is clear, but at other times, the outcome is less certain. The article concludes with a survey of other sources for debate.